Advances in the research of the mechanism of secondary resistance to imatinib in gastrointestinal stromal tumors - Hu, Xiangchen; Wang, Zhe; Su, Peng; Zhang, Qiqi; Kou, Youwei (Frontiers in Oncology, 2022)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract. At present, surgery is the first-line treatment for primary resectable GISTs; however, the recurrence rate is high. Imatinib mesylate (IM) is an effective first-line drug used for the treatment of unresectable or metastatic recurrent GISTs. More than 80% of patients with GISTs show significantly improved 5-year survival after treatment; however, approximately 50% of patients develop drug resistance after 2 years of IM treatment. Therefore, in-depth research is urgently needed to reveal the mechanisms of secondary resistance to IM in patients with GISTs and to develop new therapeutic targets and regimens to improve their long-term prognoses. In this review, research on the mechanisms of secondary resistance to IM conducted in the last 5 years are discussed and summarized from the aspects of abnormal energy metabolism, gene mutations, non-coding RNA, and key proteins. Studies have shown that different drug resistance mechanism networks are closely linked and interconnected. However, the influence of these drug resistance mechanisms have not been compared. Combination of the inhibition of drug resistance mechanisms with IM therapy and combined inhibition of multiple drug resistance mechanisms are expected to become new therapeutic options in the treatment of GISTs. In addition, implementing individualized therapies based on the identification of resistance mechanisms will provide new adjuvant treatment options for patients with IM-resistant GISTs, thereby delaying the progression of GISTs. Previous studies provide theoretical support for solving the problems of drug resistance mechanisms. However, most studies on drug resistance mechanisms are still in the research stage. Further clinical studies are needed to confirm the safety and efficacy of the inhibition of drug resistance mechanisms as a potential therapeutic target.